If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -6 + 12k = 7 + -8k + 9 + -1k Reorder the terms: -6 + k + 12k = 7 + -8k + 9 + -1k Combine like terms: k + 12k = 13k -6 + 13k = 7 + -8k + 9 + -1k Reorder the terms: -6 + 13k = 7 + 9 + -8k + -1k Combine like terms: 7 + 9 = 16 -6 + 13k = 16 + -8k + -1k Combine like terms: -8k + -1k = -9k -6 + 13k = 16 + -9k Solving -6 + 13k = 16 + -9k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '9k' to each side of the equation. -6 + 13k + 9k = 16 + -9k + 9k Combine like terms: 13k + 9k = 22k -6 + 22k = 16 + -9k + 9k Combine like terms: -9k + 9k = 0 -6 + 22k = 16 + 0 -6 + 22k = 16 Add '6' to each side of the equation. -6 + 6 + 22k = 16 + 6 Combine like terms: -6 + 6 = 0 0 + 22k = 16 + 6 22k = 16 + 6 Combine like terms: 16 + 6 = 22 22k = 22 Divide each side by '22'. k = 1 Simplifying k = 1
| 2(x+5)=2(x-5) | | -8n+(1+5n)=-6n | | K+0.6=3.84 | | -x-3=3x+33 | | (8m-8n)(4m-7n)= | | 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) | | -x+1=3x+21 | | 6X-1Y=18 | | 2(4c-1)=8c-2 | | x-2x-3=-x+9 | | 2s+8=22 | | 3(5x-4)-8x=7x-12 | | -7x+14=49-2x |